Chemistry-Assisted Proteomic Profiling of O-GlcNAcylation - Zhu, Qiang; Yi, Wen (Frontiers in Chemistry, 2021)
The modification on proteins with O-linked N-acetylglucosamine (O-GlcNAcylation) is essential for normal cell physiology. Dysregulation of O-GlcNAcylation leads to many human diseases, such as cancer, diabetes and neurodegenerative diseases. Recently, the functional role of this modification in different physiological states has been revealed due to the booming detection technologies. Chemical approaches for the enrichment of O-GlcNAcylated proteins combined with mass spectrometry-based proteomics enable the profiling of protein O-GlcNAcylation in a system-wide level. In this review, we summarize the recent progresses on the enrichment and proteomic profiling of protein O-GlcNAcylation.